Pengaruh Kebijakan Desentralisasi Terhadap Peningkatan Kesejahteraan Masyarakat Daerah - Alfarid Fadhil Rachmad; Ezra Azaria; Qika Nur Xusan; Nabillah Azzahra (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
The study discussed the impact of decentralized policies on the increasing public welfare in the region. The main focus of the article is the decentralized policies adopted and their impact on public welfare. Policy changes, power transfers, and resource allocation asa result of decentralized policies are also described. Research shows the correlation between decentralized policies and community welfare indicators, such as income, access to public services, and poverty index. The policy implications of research findings are interpreted and recommended policy actions to strengthen positive relations between decentralized policies and public welfare. In conclusion, it is concluded that decentralized policies potentially promote community welfare in the region. This article also highlights the limits of research and provides direction for future research in this field. Thus, the article provides insight into the impact of decentralized policies on the increasing of community welfare and also to an understanding of the importance of decentralized policies in boosting community welfare. Keywords: decentralized policies, community welfare, regional improvements.